The Effectiveness of Differentiated Learning using the TaRL (Teaching at the Right Level) Approach for Improving Learning Interest and Learning Outcome - Afandi, Rahmad Alvian; Ningtyas, Nindita Sabila; Susiyawati, Enny; Pratiwi, Purwanita (Jurnal Pijar Mipa, 2024)
This research was motivated by the low interest in learning and the low learning outcomes of students. This is because the learning that is carried out does not follow the students' wishes and ability level, so students are less active and have a low interest in learning science. Learning interests will affect the learning outcomes of students. This class action research aims to improve learning outcomes and students' interest in learning by using differentiated learning using the TaRL approach with the help of the inquiry learning model. TaRL learning is learning by grouping students according to their ability level. This study was conducted at SMPN 49 Surabaya in class 8B. The research data collection method used a questionnaire about students' interest in learning, an observation sheet for the implementation of learning, and a written test to determine students' learning outcomes. The design used in this study was the Tagart and Kemmis cycle model, and the data obtained was analyzed using classical learning completeness. The results showed that differentiated learning using the TaRL approach improved student learning outcomes with a percentage increase of 37% and an increase in the average score of 17.10. In addition, the results showed that students' interest in learning experienced a rise in categories from the initial condition, which had a poor category, to a good category at the end of the cycle. Based on the study's results, it can be concluded that applying differentiated learning using the TaRL approach can improve learning outcomes and student interest in the learning cycle.